2021
DOI: 10.3389/fpsyg.2021.723281
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Strategies and Textual Genres in the Teaching and Evaluation of Advanced Reading Comprehension (ARC)

Abstract: In the last decade, published data on the performance of Colombian students have concerned educators and researchers, making critical reading one of the priorities of Colombian education. That is why this article presents the results of a study carried out in a Latin American university in which the perceptions of students and professors are analyzed regarding the strategies and textual genres used to work and cross-evaluate the advanced reading comprehension (ARC). This study is materialized in the applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(65 reference statements)
1
1
0
Order By: Relevance
“…In congruence with the finding of Yan (2018) , García-Sánchez and García-Martín (2021) , and Parra et al (2021) , this study showed a positive correlation between cognitive and metacognitive strategies of learners with their writing performances. Compatible with the findings of Díaz Larenas et al (2017) and Rahayu (2021) , this study also showed that metacognitive and cognitive strategies would benefit EFL learners’ writing performance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In congruence with the finding of Yan (2018) , García-Sánchez and García-Martín (2021) , and Parra et al (2021) , this study showed a positive correlation between cognitive and metacognitive strategies of learners with their writing performances. Compatible with the findings of Díaz Larenas et al (2017) and Rahayu (2021) , this study also showed that metacognitive and cognitive strategies would benefit EFL learners’ writing performance.…”
Section: Discussionsupporting
confidence: 91%
“…Learners directly use direct strategies in the learning process to produce the target language. These strategies include memory strategies which are responsible for retrieving and storing information, cognitive strategies which learners use to process new information; and learners use compensation strategies to compensate for lack of enough knowledge in the target language ( Goudarzi et al, 2015 ; García-Sánchez and García-Martín, 2021 ; Zarrinabadi et al, 2021 ). As Oxford (1990) states, these strategies assist students to be more independent, identify their learning strengths and weaknesses, and be self-reliant in their language learning process.…”
Section: Review Of Literaturementioning
confidence: 99%